Training Needs for the Digital Teacher - Bader, Suzan Ahmad (Journal of Educational and Psychological Sciences, 2021)
Using digital technologies has become an urgent demand in this ever-changing world. The change in teachers’ role; from traditional to digital, requires systematic procedures and training. This study explores the importance of defining the training needs, the strategies of enclosing these needs, the types of training and the process of designing the training course. It also investigates the reasons that forces this change in the teacher’s role and the competencies and skills they should be equipped with.
Keywords: training needs; digital teacher; e-learning